Analysis of the Global Environmental Crisis in the Perspective of Maqasid Sharia: Efforts to Realize Sustainable Development - Pephitasya Juliana; Andi Ahmad Dhiyauddin; Radina Fauzi; Murtiadi Awaluddin; Sudirman (LP2M IAIN Palopo, 2026)
The global environmental crisis is a serious threat to the sustainability of human life, economic stability, and the balance of the world's ecosystems. Rising global temperatures, air pollution, water pollution, and biodiversity loss show that environmental issues require a multidisciplinary approach that is not only technical, but also ethical and normative. In an Islamic perspective, maqasid sharia provides a value framework that aims to realize benefits and prevent damage. This research aims to analyze environmental issues through the perspective of maqasid sharia by emphasizing the five main goals of sharia: protecting religion, soul, intellect, descent, and property. The method used is a literature study with a descriptive-analytical approach from classical sources and cutting-edge references. The results of the study show that environmental protection is an integral part of the sharia goals and is relevant to be applied in today's sustainable development policies..